Assessment of riverbank filtration performance for climatic change and a growing population - Abd-Elaty, Ismail; Kuriqi, Alban; Ganayem, Hala M.; Ahmed, Ashraf; Saleh, Osama K.; Garrote, Luis (Frontiers in Environmental Science, 2023)
Riverbank filtration (RBF) is a green drinking water production for many regions and is used as a pre-treatment phase. This study is applied to the RBF site at Embaba, Nile delta, Egypt, to model and evaluate the water budget for the RBF system by 2030, 2040, and 2050. The study was simulated to present a new method for predicting the sharing of river bank considering three cases: (i) the river stage, the RBF pumping, and the groundwater levels conditions by applying groundwater flow and solute transport using Visual MODFLOW and MT3D, respectively. The results showed that the RBF sharing (RBFS) is a proportion of the river leakage inflow in which the decreasing of the river stage due to the influence of climate change decreased the river leakage inflow and RBFS, also increasing the RBF pumping and decreased the groundwater levels due to the increase in the future drinking water pumping for the population growth was increased the river leakage inflow and the RBFS, finally combine of three cases was decreased RBFS at the future 2030, 2040 and 2050 respectively due to more sharing from groundwater compare with river inflow. The results of the current study showed that the water budget is a good tool to investigate the RBFS compared with MT3D results. This technique can reduce the cost of water quality collection and analysis; moreover, it will help with the estimation of RBF and save time compared with the solute transport modeling.